Does Education Can Explain Economic Growth? Contribution of Old And New Approach - Reza, Faizal (LPPM University 17 Agustus 1945 Samarinda, 2017)
Does education can explain economic growth? The aim of this study is to find out the impact of education on economic growth with two different approach that is the old approach called Augmented Solow Model (Neoclassical Growth Theory) and newer approach called New Growth Theory. Many research used this two model and found different result, in broad outline there are still two conclusion about impact education on economic growth. First, many researcher still conclude that education is one of important variable that influence economic growth, and vice versa. Apart from the fact that education still give two conclusion, New Growth Theory with TFP serves a broader view about what channel that used by education to influence economic growth that is from diffusion and innovation.